Given the barriers and complexities of developing applications for Clinical Commissioners within the NHS, what could be the killer application? - Steele, Diane (2013)
This report presents research into the barriers and complexities that exist when seeking to develop applications for Clinical Commissioners within the current health service; the research has been undertaken with a view to identifying an application idea that might be regarded as a killer application - an application that offers a viable commercial opportunity that is far reaching in impact and can make a real difference to Clinical Commissioners.